Follicular dendritic cell sarcoma and invasive carcinoma of the breast - David Parada, MD; Karla B. Peña, MD; Francesc Riu, MD; Luis A. Colomo Saperas, MD (Elsevier, 2017)
Follicular dendritic cell sarcoma (FDCS) is an extremely rare neoplasm derived from antigen-presenting cells. It behaves as an intermediate grade sarcoma and has high risk of local recurrence and may metastasize. We report the case of a 39-year-old woman who presented with a left mammary mass, and underwent a left mastectomy and axillary lymph node dissection. Histopathological studies were consistent with the diagnosis of FDCS and high grade breast carcinoma, both tumors involving the breast and the axillary lymph nodes. Such association has not been previously described and therefore, FDCS might be considered in the differential diagnosis of breast tumors. We also review the previous cases reported in the literature involving the breast. Keywords: Follicular dendritic sarcoma, Accessory cells, Neoplasm, Breast, Cancer